2011
DOI: 10.1271/bbb.100853
|View full text |Cite
|
Sign up to set email alerts
|

Thein Vivoandin VitroStimulatory Effects of Cordycepin on Mouse Leydig Cell Steroidogenesis

Abstract: Cordycepin, a pure compound of Cordyceps sinensis (CS), is known as an adenosine analog. We have found that CS stimulated Leydig cell steroidogenesis. Here we investigated the in vivo and in vitro effects of cordycepin in primary mouse Leydig cell steroidogenesis. The results indicate that cordycepin increased the plasma testosterone concentration. Cordycepin also stimulated in vitro mouse Leydig cell testosterone production in dose- and time-dependent manners. We further observed that cordycepin regulated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 57 publications
1
36
0
3
Order By: Relevance
“…Hsu et al [2003b] also proved that C. sinensis could activate the cAMP-protein kinase-A signal pathway. Cordycepin, as adenosine analogues, was associated with adenosine receptors to activate cAMP-PKA-Star pathway and steroidogenesis in mouse Leydig cells [Leu et al 2011]. However, Pao et al [2012] reported that cordycepin could activate intracellular PLC/PKC and MAPK signal transduction pathways, but not PKA and PI3K, to induce MA-10 cell steroidogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Hsu et al [2003b] also proved that C. sinensis could activate the cAMP-protein kinase-A signal pathway. Cordycepin, as adenosine analogues, was associated with adenosine receptors to activate cAMP-PKA-Star pathway and steroidogenesis in mouse Leydig cells [Leu et al 2011]. However, Pao et al [2012] reported that cordycepin could activate intracellular PLC/PKC and MAPK signal transduction pathways, but not PKA and PI3K, to induce MA-10 cell steroidogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…The nucleoside derivative 3′-deoxyadenosine—also called “cordycepin”—has been described in the past as an active ingredient of C. sinensis extracts787980. Studies have shown that synthetic cordycepin produces anti-inflammatory effects on cultured cells818283.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts showed the superior effect on the inhibition of linoleic peroxidation with an inhibition rate over 90%, slightly lower scavenging activities on superoxide anion and hydroxyl radicals than that of BHT, DPPH scavenging activities over 80% inhibition and moderate reducing power and ferrous ion chelating activity (Dong & Yao, 2007) (Fig.4). Huang, Chuang, Chen, & Leu, 2000;Huang, Hsu, Tsai, Sheu, & Leu, 2001;Jen et al, 2011;Leu, Poon, Pao, & Huang, 2011;Pao, Pan, Leu, & Huang, 2012;Yoshikawa et al, 2011). CHWE -Cordycepin content in hot water extract of Cordyceps sinensis; PLC -Phospholipase C; PKC -Protein kinase C; Apaf 1 -Apoptotic peptidase activating factor 1; PIP2 -phosphatedylinositolbisphosphate; DAG -Diacyleglycerol.…”
Section: 3mentioning
confidence: 99%